Burden of upper gastrointestinal cancers in the east of Golestan province (Golestan cohort study) - Mohammad‐Ali Jahani; Raziyeh Esmaeili; Mahdi Abbasi; Hossein‐Ali Nikbakht; Habibollah Azarbakhsh; Gholamreza Roshandel; Sahar Delavari; Layla Shojaie; Ghahraman Mahmoudi (Cancer Reports, 2024)
Abstract Background Cancers, especially Upper Gastrointestinal Cancers (UGCs), pose a substantial burden on society, particularly in developing nations. Golestan province, Iran, is known for its high UGC rates globally. Aims This study delves into the disease burden of UGCs in the eastern part of Golestan province. Methods and Results This study was conducted using the results of the Golestan cohort study. 2711 patients participating in this cohort, who visited Atrak Clinic during 2001–2020, participated in this study. After excluding patients with incomplete records, 2481 patients were included in the study. To compute the metrics of years of life lost (YLL), years of life lived with disability (YLD), and disability‐adjusted life years (DALY), we utilized the World Health Organization's standard life table, stratified by age and gender. The majority of UGC patients in our study were married (81.8%), had limited formal education (82.6%), and were predominantly male (61.1%). A substantial proportion resided in suburban areas (85.8%), and over half of the patients (52%) reported a history of drug addiction. The mean age at diagnosis for men was 65.76 years with a standard deviation of 11.34, while for women, it was 64.38 years with a standard deviation of 11.66. Regarding disease impact, YLL, YLD, and DALY for men were 21 240, 1956, and 23 196 (307.8 per 100 000), respectively. For women, these figures were 15 609 for YLL, 1367 for YLD, and 16 976 (223.1 per 100 000) for DALY. Conclusion After the increasing trend of the burden of UGCs in Golestan province in the early years of the study, this rate has been decreasing in recent years. Effective strategies necessitate collaborative efforts across various sectors to alleviate this burden, focusing on preventive measures, timely diagnosis, and well‐coordinated therapeutic interventions.